The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10854-020-04994-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvents and annealing treatment on the properties of the methylammonium lead tribromide perovskite thin films

Abstract: Solution-processed hybrid organic-inorganic perovskites from organoammonium halide and lead halide precursors form effective active layers for optoelectronics devices. The solvent plays a decisive factor on the preparation of active layer for perovskite application. In this report, the properties of methylammonium lead tribromide (MAPbBr 3) thin films were studied using various solvents. The solvents used were dimethylformamide (DMF), dimethyl sulfoxide (DMSO), a mixture of DMF ? IPA (Isopropanol). The photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several processing techniques have been proposed as effective methods for controlling the quality of perovskite layers, including solvent treatment methods, annealing methods [13] using temperature and humidity to form crystals, controlling the proportion of perovskite solution, moisture-assisted growth, additives, and hot spin-coating [14][15][16]. Moreover, the dependence of the morphological and optical properties on the deposition method used to prepare perovskite films has been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several processing techniques have been proposed as effective methods for controlling the quality of perovskite layers, including solvent treatment methods, annealing methods [13] using temperature and humidity to form crystals, controlling the proportion of perovskite solution, moisture-assisted growth, additives, and hot spin-coating [14][15][16]. Moreover, the dependence of the morphological and optical properties on the deposition method used to prepare perovskite films has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Jeon et al reported the solution processing of efficient PSCs comprising a bilayered architecture and MAPb(I 1−x Br x ) 3 perovskites formed using SET [34]. In another reports [13], the optical (UV-vis and PL) and structural (IR) properties were found to be highly dependent on the perovskite layer prepared with different solvents. Another group has presented a set of solubility data for MAPbBr 3 , FAPbBr 3 MAPbI 3 , and FAPbI 3 , perovskites in DMF and DMSO, and they rationalize the observed differences in solubility by analyzing the donor numbers of the solvents and halide anions [35].…”
Section: Introductionmentioning
confidence: 99%